Mówić inaczej, czyli tak samo. Język w przestrzeni politycznej państwa totalitarnego i demokratycznego - Ożóg, Sławomir (Słowo. Studia językoznawcze, 2010)
This article is an attempt to find, among the political language, a democratic state that Poland is today, those features and functions that were identified with the communist ‘newspeak’ by linguists. It is the attempt to prove that those two ways of talking about public issues are similar. The analysis of the linguistic material proves the statement that contemporary political language is as well pragmatic, ritual, magical and idiomatic as the newspeak. Furthermore, the basic features that were supposed to show a specific character of communist newspeak are easy to separate in today’s political discourse. What is more, the article presents those semantic fields that are common political language in democratic and totalitarian state.